Opportunities for cultural tourism in the Transylvanian-Hegyalja region today - Elekes, Tibor; Szilágyi, Ferenc (Acta Carolus Robertus, 2022)
The Transylvanian-Hegyalja is a hilly region located in the southwestern part of historical Transylvania, between the Erdélyi-szigethegység/Apuseni Mountains and the Maros/Mureş River. The area with its advantageous natural and socio-geographic features and varied history preserves extraordinary cultural values. Its historical and cultural center is the Castle of Gyulafehérvár. The ecclesiastical and secular buildings and monuments of the castle are cultural achievements of the Roman era, the Kingdom of Hungary, the Principality of Transylvania, the Habsburg Empire, the Austro-Hungarian Monarchy and the post-World War I Romania. Before 1990, it was mostly possible to visit memorial sites and monuments related to Romanian history. The university founded in 1991 to commemorate the historic event in Gyulafehérvár on December 1, 1918, uses some of the buildings in the territory of the castle. The cultural values ​​restored with the support of the European Union between 2013-2015 were integrated into the tourist offer, vividly describing the Habsburg period of the city's history. The Cathedral of the Transylvanian Roman Catholic Bishopric, founded in 1009, the Pantheon of Transylvania, preserves the ecclesiastical, historical and architectural values ​​of several centuries.The Reformed academy building in the castle, the priceless Batthyaneum library, and the remains of the 10th century church are not open to the public these days. Making them accessible to visitors would significantly increase the tourist facilities and opportunities of the city and the region.
Keywords: cultural tourism; the Castle of Gyulafehérvár; Transilvania